2019
DOI: 10.4014/jmb.1902.02034
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Fermented Extract of Chaga-Cheonggukjang Attenuates the Effects of Obesity and Suppresses Inflammatory Response in the Liver and Spleen of High-Fat Diet-Induced Obese Mice

Abstract: Cheonggukjang and chaga mushrooms have numerous health benefits, and have been used in alternative medicine. Therefore, a powder mixture of 98: Cheonggukjang and 2: Chaga extracts was fermented with Lactobacillus acidophilus KCTC3925 (FCC) and its anti-obesity effects in high-fat diet (HFD)-induced obese mice were determined. Five-week-old male ICR mice were fed a normal diet or HFD in the presence or absence of 3% and 5% FCC by weight (n = 10 per group). After 12 weeks, the mice were sacrificed, and the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…S2) significantly inhibited the Nile red fluorescence at 100 and 25 μg/mL and extended the mean survival rate of worms with a significant DT 50 increase of 43.1% and 33.3%, at 100 and 25 µg/mL, respectively (Table 2). Our findings are in line and complement recent preclinical studies on the beneficial effects of I. obliquus extracts in different mammal models of obesity and diabetes [73][74][75][76] . Longevity effects of I. obliquus in C. elegans were already reported by Scerbak et al 77,78 , and in Drosophila melanogaster by Zhang et al 79 .…”
Section: Survival Assaysupporting
confidence: 91%
“…S2) significantly inhibited the Nile red fluorescence at 100 and 25 μg/mL and extended the mean survival rate of worms with a significant DT 50 increase of 43.1% and 33.3%, at 100 and 25 µg/mL, respectively (Table 2). Our findings are in line and complement recent preclinical studies on the beneficial effects of I. obliquus extracts in different mammal models of obesity and diabetes [73][74][75][76] . Longevity effects of I. obliquus in C. elegans were already reported by Scerbak et al 77,78 , and in Drosophila melanogaster by Zhang et al 79 .…”
Section: Survival Assaysupporting
confidence: 91%
“…Further, fermentation carried out by B. subtilis or B. licheniformis can also exert antimicrobial effects on pathogenic bacteria in the gut, reduce the activities of intestinal bacteria, and mediate the release of harmful substances through adsorption [ 2 , 10 ]. Novel nutritional, sensory, and bioregulatory functions produced during the microbial fermentation of CGJ, which were initially absent in the base ingredient, have been reported in previous studies [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These novel bioactive substances mediate the functions of CGJ, such as thrombolysis [ 43 ], hypertension prevention [ 41 ], improved lipid metabolism [ 44 ], antimutagenic and anticancer activities [ 24 ], and antimicrobial effects [ 45 ].…”
Section: Bioactivities and Human Health Benefits Of Cgjsupporting
confidence: 57%
“…In addition to antioxidant effects, CGJ has been shown to have anti-inflammatory effects. As shown Table 5 and Figure 7 , CGJ improves anti-inflammatory activity by regulating the expression of genes associated with NF-κB-mediated inflammation and by increasing the production of hyaluronic acid in mice [ 20 , 44 ], RAW264.7 macrophage, HaCaT cells [ 125 ], and SD rats [ 4 , 120 ]. Validation of the safety of CGJ extracts through biological experiments can render the use of such extracts possible as natural antioxidant and anti-inflammation agents in food products such as edible oils.…”
Section: Bioactivities and Human Health Benefits Of Cgjmentioning
confidence: 99%
“…These beneficial effects of mushrooms on human health are attributed to a large number of secondary metabolites in their extracts. A variety of investigations into mushrooms have demonstrated that mushroom extracts or their metabolites, such as polysaccharides, oligopeptides, polyphenols, and fibers, significantly reduce hypertension, atherosclerosis, lipid accumulation, and obesity [31][32][33]. In addition to these previous works, we here identified the efficacy of vulpinic acid, a mushroom-derived metabolite from P. ravenelii, on the formation of adipocytes and osteoblasts.…”
Section: Discussionmentioning
confidence: 58%